AUSTRALIA’S ROLE IN DEVELOPING INDONESIA’S CAPACITY BUILDING IN COMBATTING NARCOTIC CRIMES - sholihah, Fetty Fidyatus; Hidayatullah, Nur Luthfi (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
This research seeks to explain Australia's role, through the Australian Federal Police (AFP) and the Australian Border Force (ABF) in developing Indonesian National Narcotics Board’s (BNN) capacity building in dealing with narcotics crimes. Special skills are needed in dealing with narcotics crimes, both in the process of prosecution of criminals and crime prevention. The Indonesian National Narcotics Board faced several obstacles in handling narcotic crimes, including the lack of capacity in using technology to identify new kinds of drugs and capability to track down narcotic criminals. Hence, Australia observes that enforcement skills could be developed within Indonesia's capacity to deal with narcotics crimes. This study uses a descriptive research method with a qualitative approach to describe Australia’s role in developing Indonesia's internal and external capacity building.The result of this research shows that Australia's role in developing Indonesia's capacity building through conducting activities in the form of training which consists of skills, knowledge and attitude training. Australia’s training has improved BNN staff’s internal capacity in problem solving, integrity and knowledge. Australia has also improved BNN’s external capacity by developing K-9 facilities and granting dog runs.